LIG / Fe3O4 / Mn3O4 composite material, preparation method and application thereof, and supercapacitor
By using the LIG/Fe3O4/MN3O4 composite material prepared in the supercapacitors, the performance of the FE3O4 electrode material is not ideal, and the performance of the super capacitor performance of high capacitors, high energy density and good cycle stability is realized.
Patent Information
- Application Number
- CN202411129585.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing Fe3O4 electrode materials have the disadvantages of low conductivity, poor stability, large capacity loss, and easy agglomeration, which leads to their poor performance in supercapacitors.
By compounding the polymer substrate with an iron source and a manganese source, and preparing a LIG/Fe3O4/Mn3O4 composite material under laser irradiation, an in-situ composite structure is formed to improve the conductivity and stability of the electrode material.
The high capacitance, high energy density and good cycle stability of the supercapacitor are achieved, and the operating voltage window is expanded, allowing it to exhibit excellent electrochemical performance in the voltage range from -1V to 1V.
Smart Images

Figure CN119340121A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a laser-induced graphene / ferroferric oxide / manganese tetraoxide (LIG / Fe 3 O 4 / Mn 3 O 4 ) Composite materials, preparation methods and uses thereof, and supercapacitors. Background Art
[0002] With the rapid development of global economy, energy depletion and environmental pollution are becoming increasingly prominent. It is particularly important to develop new electrochemical energy storage devices with high power and energy density, stable and long-lasting and environmentally friendly. Among them, supercapacitors have attracted widespread attention due to their short charging time, long cycle life, high power density, high energy density and high safety.
[0003] Metal oxides are common electrode materials for supercapacitors, among which Fe 3 O 4 It has become an excellent electrode material due to its easy preparation, high capacitance, suitable working voltage window, low cost, abundant resources and non-toxicity. 3 O 4 At the same time, it has the disadvantages of low conductivity, poor stability, large capacity loss, and easy agglomeration. Therefore, pure Fe 3 O 4 As an electrode material, the material has an unsatisfactory specific capacitance, high resistance, poor rate performance, and low cycle life. 3 O 4 Composite with carbon materials with good conductivity can improve this problem.
[0004] Among carbon materials, graphene has attracted great attention in various research fields due to its high stability, high conductivity and high surface area. Many methods have been developed to prepare graphene, such as mechanical exfoliation, chemical vapor deposition, reduced graphene oxide, etc. However, these methods have disadvantages such as low productivity, high preparation conditions, high energy consumption and environmental pollution, and cannot meet the requirements of low-cost and scalable production. Graphene (LIG) prepared by laser induction exhibits excellent properties such as high porosity, high thermal stability, good conductivity, economic and environmental protection, and designable patterns. By changing the preparation conditions to control the microstructure and defect density of graphene, the electrode-related properties can be improved, which is conducive to the composite with subsequent materials.
[0005] In order to make up for the shortcoming of narrow voltage window, the present invention adopts LIG / Fe 3 O 4 On the basis of the composite material, manganese oxide, which can provide a positive potential, is further added to prepare LIG / Fe 3 O4 / Mn 3 O 4 Composite materials are called integrated electrode materials. Research results show that integrated electrode materials integrate traditional positive and negative electrode materials, can work across positive and negative voltage windows, achieve a voltage span from -1V to 1V, achieve a significant increase in the operating voltage range, and exhibit excellent electrochemical performance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a LIG / Fe 3 O 4 / Mn 3 O 4 Composite material and preparation method thereof, under the action of laser irradiation, the polymer substrate is converted into graphene, and the iron source is converted into Fe 3 O 4 , the manganese source is converted into Mn 3 O 4 , forming an in-situ composite structure; and the preparation method has easy-to-obtain raw materials, simple operation, short time, and less pollution, can meet different application requirements, and is easy to promote; at the same time, the composite material can be used for the preparation of supercapacitors, so that the supercapacitors have high capacitance, high energy density and good cycle stability.
[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0008] The first object of the present invention is to provide a LIG / Fe 3 O 4 / Mn 3 O 4 The method for preparing the composite material comprises the following steps:
[0009] (1) Compounding the polymer substrate with an iron source and a manganese source to obtain a polymer substrate containing iron and manganese elements;
[0010] (2) Laser irradiation of a polymer substrate containing iron and manganese elements to obtain LIG / Fe 3 O 4 / Mn 3 O 4 Composite materials.
[0011] The second object of the present invention is to provide a LIG / Fe 3 O 4 / Mn 3 O 4 LIG / Fe composite material obtained by the preparation method 3 O 4 / Mn 3 O 4Composite materials.
[0012] The third object of the present invention is to provide the LIG / Fe 3 O 4 / Mn 3 O 4 Use of composite materials as electrode materials.
[0013] The fourth object of the present invention is to provide a supercapacitor using the LIG / Fe 3 O 4 / Mn 3 O 4 Composite materials as electrode materials.
[0014] The beneficial effect of the present invention is that the present invention prepares LIG / Fe by laser irradiating a polymer substrate containing iron and manganese elements. 3 O 4 / Mn 3 O 4 Composite materials, giving full play to LIG, Fe 3 O 4 and Mn 3 O 4 The advantages in the application field of supercapacitors provide guarantees for the capacitance performance of supercapacitors, making supercapacitors have the advantages of wide voltage window, high specific capacity, high energy density, good cycle stability, etc., which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 SEM images of composite materials;
[0016] Figure 2 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Pore size distribution diagram of composite materials;
[0017] Figure 3 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Composite material, LIG / Fe prepared in Comparative Example 1 3 O 4 Water contact angle images of the composite material and LIG prepared in Comparative Example 2;
[0018] Figure 4 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Composite material and LIG / Fe prepared in Comparative Example 1 3 O 4 XRD patterns of composite materials;
[0019] Figure 5 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Composite material and LIG / Fe prepared in Comparative Example 1 3 O 4 CV curves of the composite material as electrode material at different scan rates and GCD curves at different current densities;
[0020] Figure 6 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 CV curve, GCD curve, EIS curve, and area specific capacitance diagram of the composite material as electrode material;
[0021] Figure 7 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 CV curve, GCD curve, EIS curve, and area specific capacitance diagram of supercapacitors assembled with composite materials as electrode materials;
[0022] Figure 8 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Cycle life and coulombic efficiency of supercapacitors assembled with composite materials as electrode materials. DETAILED DESCRIPTION
[0023] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0024] The present invention provides a LIG / Fe 3 O 4 / Mn 3 O 4The method for preparing the composite material comprises the following steps:
[0025] (1) Compounding the polymer substrate with an iron source and a manganese source to obtain a polymer substrate containing iron and manganese elements;
[0026] (2) Laser irradiation of a polymer substrate containing iron and manganese elements to obtain LIG / Fe 3 O 4 / Mn 3 O 4 Composite materials.
[0027] In a further technical solution, the polymer substrate includes but is not limited to one or more of carbon chain polymers, heterochain polymers, alicyclic polymers, aromatic polymers, fruits and vegetables, and animal fur.
[0028] In a further technical solution, the iron source includes but is not limited to one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0029] In a further technical solution, the manganese source includes but is not limited to one or more of manganese carbonate, manganese acetate, and potassium permanganate.
[0030] In a further technical solution, the composite method of the polymer substrate and the iron source and manganese source includes but is not limited to one or more of dipping, rolling, spraying, and brushing. When the polymer substrate is impregnated with the iron source and manganese source solution, ultrasonic treatment can be performed simultaneously to facilitate the iron source and manganese source to be immersed in the polymer substrate as much as possible. In addition, deionized water or ethanol can be used as a solvent to prepare the iron source and manganese source solution. Compared with deionized water, ethanol can better improve the degree of iron source and manganese salt immersion in the polymer substrate, so that the polymer substrate can accommodate more iron source and manganese source. Since the polymer substrate is not conductive, there will be no Fe 3 O 4 and Mn 3 O 4 Sedimentation.
[0031] In a further technical solution, the laser includes but is not limited to one or more of a gas laser, a solid laser, a semiconductor laser, a fiber laser, a pulsed laser, a continuous laser, and an excimer laser.
[0032] In a further technical solution, the laser irradiation conditions include: wavelength of 10.6 μm, power of 12 to 16 W, frequency of 10 to 100 kHz, energy density of 0.1 to 10 J / cm 2 , the scanning rate is 60~100mm / s. By controlling the parameters of laser irradiation, Fe 3 O 4 , Mn 3 O4 Uniformly doped graphene composites.
[0033] The present invention provides a method of forming a LIG / Fe 3 O 4 / Mn 3 O 4 LIG / Fe composite material obtained by the preparation method 3 O 4 / Mn 3 O 4 Composite materials.
[0034] In some specific embodiments, the LIG / Fe 3 O 4 / Mn 3 O 4 The hydrophilic contact angle of the composite material is 0°. 3 O 4 / Mn 3 O 4 The composite material is super hydrophilic, which is conducive to the infiltration of electrolyte.
[0035] The present invention provides the LIG / Fe 3 O 4 / Mn 3 O 4 The use of the composite material as an electrode material. 3 O 4 / Mn 3 O 4 Composite materials are used as electrode materials to fully utilize their excellent electrochemical properties.
[0036] The present invention provides a supercapacitor using the LIG / Fe 3 O 4 / Mn 3 O 4 The composite material is used as an electrode material. The supercapacitor can be assembled using conventional methods known in the art.
[0037] Example 1
[0038] a. Preparation of PI sheet substrate containing iron and manganese elements
[0039] Weigh 6g of ferric chloride particles and 2g of manganese carbonate powder, prepare an iron-manganese solution with a concentration of 0.1mol / L with deionized water, and stir to evenly disperse the ferric chloride and manganese carbonate particles in the deionized water. Select a density of 10kg / cm 3A 1 cm thick polyimide (PI) foam was used as the substrate, immersed in the above-prepared iron-manganese solution, and ultrasonically treated for 2 hours. The fully immersed PI foam was placed in a vacuum oven at 80°C for drying, and then pressed into a sheet under a pressure of 30 MPa to obtain a PI sheet substrate containing iron and manganese elements.
[0040] b. Using laser induced technology to produce LIG / Fe 3 O 4 / Mn 3 O 4 Preparation of composite materials
[0041] The wavelength of CO is 10.6 μm. 2 Infrared laser marking machine, power set to 14W, scanning speed set to 80mm / s, frequency set to 20kHz, energy density set to 5J / cm 2 The PI sheet substrate containing iron and manganese elements was placed on the workbench of the laser marking machine in an air atmosphere and scanned according to the set line to obtain LIG / Fe 3 O 4 / Mn 3 O 4 Composite materials.
[0042] Figure 1 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 SEM images of composite materials. Figure 1 The needle-shaped Fe 3 O 4 and Mn 3 O 4 The particles are distributed in the graphene structure.
[0043] Figure 2 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Pore size distribution of the composite material. Figure 2 It can be seen that the composite material has a rich pore size distribution, including macropores, mesopores and micropores, which is beneficial to improving the ion transmission capacity.
[0044] Comparative Example 1
[0045] The difference between Comparative Example 1 and Example 1 is that the manganese source is not composited on the polymer substrate.
[0046] a. Preparation of PI sheet substrate containing iron
[0047] Weigh 6g of ferric chloride particles and prepare a 0.1mol / L iron salt solution with deionized water. Stir to evenly disperse the ferric chloride particles in the deionized water. Select a density of 10kg / cm 3 The PI foam with a thickness of 1 cm was used as the substrate, immersed in the iron solution prepared above, and ultrasonically treated for 2 hours. The fully immersed PI foam was placed in a vacuum oven at 80°C for drying, and then pressed into a sheet under a pressure of 30 MPa to obtain a PI sheet substrate containing iron elements.
[0048] b. Preparation of graphene / ferroferric oxide composite materials using laser induced technology
[0049] The wavelength of CO is 10.6 μm. 2 Infrared laser marking machine, power set to 14W, scanning speed set to 80mm / s, frequency set to 20kHz, energy density set to 5J / cm 2 The above-mentioned PI sheet substrate containing iron element was placed on the workbench of the laser marking machine in an air atmosphere, and scanned according to the set line to obtain LIG / Fe 3 O 4 Composite materials.
[0050] Comparative Example 2
[0051] The difference between Comparative Example 2 and Example 1 is that the iron source and the manganese source are not composited on the polymer substrate.
[0052] a. Preparation of PI sheet substrate
[0053] Select the density as 10kg / cm 3 , 1 cm thick PI foam was used as the substrate, and a pressure of 30 MPa was applied to press it into a sheet to obtain a PI sheet substrate.
[0054] b. Preparation of laser-induced graphene:
[0055] The wavelength of CO is 10.6 μm. 2 Infrared laser marking machine, power set to 14W, scanning speed set to 80mm / s, frequency set to 20kHz, energy density set to 5J / cm 2 The PI-containing sheet substrate was placed on the workbench of a laser marking machine in an air atmosphere and scanned according to a set line to obtain LIG.
[0056] Figure 3 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Composite material, LIG / Fe prepared in Comparative Example 1 3 O4 Composite material, LIG prepared in comparative example 2, water contact angle pictures. Figure 3 It can be seen that the contact angle of LIG is close to 140°, and the contact angle of LIG / Fe 3 O 4 / Mn 3 O 4 Composites and LIG / Fe 3 O 4 The contact angle of the composite material is close to 0°, which is conducive to the subsequent penetration of electrolyte solution and the transport of ions.
[0057] Figure 4 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Composite material and LIG / Fe prepared in Comparative Example 1 3 O 4 XRD pattern of the composite material. Figure 4 It can be seen that at 2θ = 30.3°, 2θ = 35.764°, 2θ = 57.511°, and 2θ = 63.1°, respectively, Fe 3 O 4 The (220), (311), (511), and (440) planes correspond to Mn at 2θ=28.9°, 2θ=32.3°, 2θ=36°, 2θ=58.5°, and 2θ=59.9°, respectively. 3 O 4 The (112), (103), (211), (321), and (224) crystal planes of graphene were observed at 2θ = 26°, which proves that the present invention successfully prepared LIG / Fe in situ by laser induction in one step. 3 O 4 / Mn 3 O 4 Composite materials.
[0058] Example 2
[0059] In this example, LIG / Fe 3 O 4 / Mn 3 O 4 The method for preparing the composite material is the same as that in Example 1, except that the laser power in step b is replaced with 12W.
[0060] Example 3
[0061] In this example, LIG / Fe 3 O 4 / Mn 3 O 4The method is the same as that of Example 1, except that the laser power in step b is replaced with 16 W.
[0062] Example 4
[0063] In this example, LIG / Fe 3 O 4 / Mn 3 O 4 The method is the same as that of Example 1, except that the concentration of the iron solution in step a is replaced with 0.3 mol / L.
[0064] Example 5
[0065] In this example, LIG / Fe 3 O 4 / Mn 3 O 4 The method for preparing the composite material is the same as that in Example 1, except that the base PI foam in step a is replaced by a PI film with a thickness of 1 mm.
[0066] Example 6
[0067] In this example, LIG / Fe 3 O 4 / Mn 3 O 4 The method for preparing the composite material is the same as that in Example 1, except that the base PI foam in step a is replaced by a phenolic resin film.
[0068] The LIG / Fe prepared in Examples 1 to 6 above 3 O 4 / Mn 3 O 4 Composite material and LIG / Fe prepared in Comparative Example 1 3 O 4 The composite material was subjected to electrochemical performance test, and the test method and test results are as follows:
[0069] The test instrument was Shanghai Chenhua Electrochemical Workstation 660D. The three-electrode system test was carried out in a lithium chloride electrolyte with a concentration of 1 mol / L (lithium chloride was dissolved in deionized water). The LIG / Fe prepared in Examples 1 to 6 was used. 3 O 4 / Mn 3 O 4 Composite material or LIG / Fe prepared in Comparative Example 1 3 O 4 The composite material was the working electrode, Ag / AgCl was the counter electrode, and Pt was the reference electrode.
[0070] Figure 5 The LIG / Fe prepared in Example 1 3O 4 / Mn 3 O 4 Composite material and LIG / Fe prepared in Comparative Example 1 3 O 4 The CV curves of the composite material as an electrode material at different scan rates and the GCD curves at different current densities. Figure 5 From the CV curve of (a), we can find that compared with LIG / Fe 3 O 4 The composite material has capacitance only in the voltage range of -0.8V to 0.2V. 3 O 4 / Mn 3 O 4 The working voltage window of the composite material has been greatly broadened, no longer limited to the traditional positive voltage window or negative voltage window, and has achieved a leap between the positive voltage window and the negative voltage window. It shows excellent electrochemical performance in the positive and negative voltage range of -1V to 1V, and the area surrounded by CV is greatly expanded, which has better performance than LIG / Fe 3 O 4 The composite material has a higher area specific capacitance. Figure 5 (b) Comparison of LIG / Fe 3 O 4 / Mn 3 O 4 Composites and LIG / Fe 3 O 4 GCD curve of the composite material shows that LIG / Fe 3 O 4 The discharge time of the composite material in the potential range of -0.8V to 0.2V reaches 17s, while LIG / Fe 3 O 4 / Mn 3 O 4 The discharge time of the composite material in the potential range of -1V to 1V reaches 42s, which is more than 2 times longer, and the electrochemical performance is significantly improved. 3 O 4 / Mn 3 O 4 It is related to the structure of the composite material. The positive electrode material manganese oxide and the negative electrode material iron oxide are integrated in a piece of electrode material. It has the electrochemical properties of both positive electrode materials and negative electrode materials, which improves the energy storage performance.
[0071] Figure 6 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4CV curve, GCD curve, EIS curve, and area specific capacitance diagram of the composite material as electrode material. Figure 6 (a) It can be seen that the working voltage window is as wide as 2V, and the overall shape of the CV curve is similar to a rectangle, with a pair of weak redox peaks at 0.35V and 0.32V. As the scan rate changes, no obvious change is found in the shape of the CV curve, indicating that the electrode material can withstand high charge and discharge rates. Figure 6 (b) shows that the GCD curve is a triangle, showing good symmetry, and no obvious voltage drop is detected during the discharge stage, indicating that the internal resistance of the electrode material is small and ions can be quickly transported in the electrode material. The area specific capacitance of the electrode material is calculated from the GCD data, such as Figure 6 As shown in (c), at high current density (10 mA / cm 2 ) can reach 210mF / cm 2 , at low current density (1mA / cm 2 ) can reach 659mF / cm 2 This shows that the area specific capacitance remains at a high level even when the voltage window is greatly expanded. Figure 6 The Nyquist curve in (d) shows that LIG / Fe 3 O 4 / Mn 3 O 4 The composite material has a small internal resistance (5.7Ω). In addition, the Nyquist curve shows an arc in the high-frequency region, which is dominated by the charge transfer process. The smaller the radius of the arc, the smaller the charge transfer resistance; while the low-frequency region shows a straight line, which is dominated by the diffusion process. The larger the slope of the straight line, the smaller the mass transfer impedance. According to the radius of the arc and the slope of the straight line in the EIS graph, it can be judged that the composite material has a small charge transfer resistance and mass transfer resistance.
[0072] The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 The composite material was used as an electrode material to assemble an all-solid-state supercapacitor. The specific assembly process was as follows: PVA / LiCl was used as the electrolyte (preparation method: 2 mL LiCl was added to 20 mL deionized water, and then 2 g PVA (polyvinyl alcohol) was added and stirred at 85 ° C for 60 min). The electrolyte was evenly applied on the LIG / Fe 3 O 4 / Mn 3 O 4 The active area of the composite material was dried in a vacuum oven at 60 °C for 6 h. Copper foil was used as the electrode lead wire, and conductive silver glue was used to connect the copper foil and LIG / Fe 3O 4 / Mn 3 O 4 Composite materials can complete the assembly of flexible all-solid-state supercapacitors, and the electrochemical performance is tested using Shanghai Chenhua electrochemical workstation 660D.
[0073] Figure 7 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 CV curve, GCD curve, EIS curve, and area specific capacitance diagram of supercapacitors assembled with composite materials as electrode materials. Figure 7 (a) shows the CV curve of the supercapacitor (at different scan rates). The operating voltage is as high as 1.8 V. As the scan rate increases, the area enclosed by the CV curve gradually increases, and the CV curve is approximately rectangular. Figure 7 (b) shows the GCD curve of the supercapacitor (under different current densities). It can be seen that the GCD curve is triangular in shape, with no obvious voltage drop. As the current density decreases, the discharge time tends to increase. Based on the results of the GCD graph, the area specific capacitance of the supercapacitor can be calculated, such as Figure 7 (c) shows that it has 116.9mF / cm at a current density of 1mA. 2 The area specific capacitance can still maintain 60mF / cm at a current density of 2mA. 2 The area specific capacitance is 47.9 μWh / cm. 2 , the area power density is 819.2μW / cm 2 . Figure 7 (d) is the EIS curve of the supercapacitor, from which it can be seen that the supercapacitor has good ion conductivity and ion transport capability.
[0074] Figure 8 The LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 The cycle life and coulombic efficiency of supercapacitors assembled with composite materials as electrode materials. Figure 8 It can be seen that the capacity retention rate can reach 83% after 10,000 cycles, and the Coulomb efficiency is close to 100%.
[0075] According to the above test method, the LIG / Fe prepared in Examples 2 to 6 were tested respectively. 3 O 4 / Mn 3 O 4The composite material was used as an electrode material at a current density of 1 mA / cm 2 Based on the GCD curve below, the specific capacitance is calculated according to the formula, and the results are shown in Table 1.
[0076] The calculation formula of specific capacitance is:
[0077] Among them, C is the specific capacitance, I is the current density, A is the active material area of the electrode material, △t is the discharge time, and △V is the voltage range.
[0078] Table 1
[0079] <![CDATA[Specific capacitance (mF / cm 2 )]]> Example 1 659 Example 2 342 Example 3 383 Example 4 355 Example 5 331 Example 6 307
[0080] It can be seen from Table 1 that the LIG / Fe prepared in Example 1 3 O 4 / Mn 3 O 4 Composite material at 1mA / cm 2 The specific capacitance at current density is 659mF / cm 2 , which is close to twice that of other examples, indicating that only by selecting appropriate preparation conditions can LIG / Fe with excellent electrochemical performance be obtained. 3 O 4 / Mn 3 O 4 Composite materials.
[0081] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a LIG / Fe3O4 / Mn3O4 composite material, characterized in that: The following steps are involved: (1) Compounding the polymer substrate with an iron source and a manganese source to obtain a polymer substrate containing iron and manganese elements; (2) Laser irradiation of a polymer substrate containing iron and manganese elements to obtain a LIG / Fe3O4 / Mn3O4 composite material.
2. The preparation method according to claim 1, characterized in that: The polymer substrate is selected from one or more of carbon chain polymers, heterochain polymers, alicyclic polymers, aromatic polymers, fruits and vegetables, and animal fur.
3. The preparation method according to claim 1, characterized in that: The iron source is selected from one or more of ferric chloride, ferric sulfate, and ferric nitrate; the manganese source is selected from one or more of manganese carbonate, manganese acetate, and potassium permanganate.
4. The preparation method according to claim 1, characterized in that: The composite method of the polymer substrate and the iron source and the manganese source is selected from one or more of dipping, rolling, spraying and brushing.
5. The preparation method according to claim 1, characterized in that: The laser is selected from one or more of gas laser, solid laser, semiconductor laser, fiber laser, pulse laser, continuous laser and excimer laser.
6. The preparation method according to claim 1, characterized in that: The laser irradiation conditions include: wavelength of 10.6 μm, power of 12 to 16 W, frequency of 10 to 100 kHz, energy density of 0.1 to 10 J / cm 2 , the scanning rate is 60~100mm / s.
7. A LIG / Fe3O4 / Mn3O4 composite material obtained by the preparation method according to any one of claims 1 to 6.
8. The LIG / Fe3O4 / Mn3O4 composite material according to claim 7, characterized in that: The hydrophilic contact angle of the LIG / Fe3O4 / Mn3O4 composite material is 0°.
9. Use of the LIG / Fe3O4 / Mn3O4 composite material according to claim 7 or 8 as an electrode material.
10. A supercapacitor, using the LIG / Fe3O4 / Mn3O4 composite material according to claim 7 or 8 as an electrode material.